The Relationship Between Emotional Regulation and Aggressive Behavior in Adolescents at Al-Amin Orphanage, Sidoarjo District - Mujiadi; Fitriyah, Lailatul (Al-Hijrah Indonesia, 2024)
Aggressive behavior can be in the form of physical, psychological, financial, and sexual violence. Aggressive behavior that is left unchecked and does not get attention can have an impact on juvenile delinquency. This study aimed to determine the relationship between emotional regulation and aggressive behavior in adolescents. This quantitative study used a correlational analytic type of research with a cross-sectional design. The research location was in Sidoarjo. The sample consisted of 34 adolescent children aged 10-15 years living in orphanages. The sampling technique used purposive sampling, and data were collected using a questionnaire, The Buss-Perry Aggression Questionnaire, and the statistical test used was the Spearman test. The study results showed that most respondents, 19 people (55%), had aggressive verbal behavior. Almost half of 13 respondents (37%) with moderate category emotional regulation had verbal aggressive behavior. The results of the Spearman test obtained p (0.022) <α (0.05), meaning that there is a relationship between emotional regulation and aggressive behavior in adolescents. The coefficient value (r) = 0.401 means that the nature of the relationship is in the medium category and with a positive direction, meaning that the higher the ability of adolescents to regulate emotions, the lower the aggressive behavior and vice versa. There needs to be supervision from the orphanage management regarding the emotional development of their foster children and the handling of perpetrators and victims through counseling with health workers.